Auxiliary Fan Selection Considering Purchasing and Energy Costs Based on Fan Curves - Hurtado-Cruz, J (CRC PRESS-BALKEMA, 2021)
Mine ventilation practitioners are commonly tasked with estimating operating set point and selecting an auxiliary fan to supply the air required for underground operations. This static decision could be considered a subset of the larger fan selection of main and auxiliary fans, which is dynamic over the course of the mine life. It is common to have multiple fan suppliers that can deliver the same operating point with different purchasing cost and expected efficiencies as indicated in the fan curves. Historically, for the same duty point, the decision has been driven by minimum purchasing cost; however, this may not be the best option when including energy costs over a certain period. This paper presents a methodology to simultaneously evaluate the capital and energy cost of a fan based on the fan curve inputs, as a decision support tool for purchasing the cost effective fan. A case study is presented to illustrate the fan selection methodology and the impact of the energy cost and the time horizon as compared to just the minimum purchasing cost. Finally, a sensitivity analysis is performed on the key inputs to understand the extent and the validity of the conclusions derived.